Cutaneous and Systemic Psoriasis: Classifications and Classification for the Distinction - Yan, Bing-Xi; Chen, Xue-Yan; Ye, Li-Ran; Chen, Jia-Qi; Zheng, Min; Man, Xiao-Yong (Frontiers in Medicine, 2021)
Psoriasis is a chronic, multisystem, inflammatory proliferative disease affects 2-3% of the global population. The typical clinical cutaneous manifestation of psoriasis is scaly erythema or plaque, limited or widely distributed. However, psoriasis is far beyond the skin involvement and provides many challenges, including associated comorbidities like psoriatic arthritis，psoriatic metabolic syndrome，psoriatic diabetes，psoriatic cardiovascular disease，psoriatic nephropathy，psoriatic bowel disease，Psoriatic brain diseases. In this review, we classify psoriasis as cutaneous and systemic psoriasis, according to the clinical diversity and associated comorbid diseases, and recommend classification criteria for psoriasis. This novel classification criteria for psoriasis will help to better understand and manage this complex disease. The key objective of this review is to raise awareness of the complexity of this multifaceted disease, the potential of state-of-the-art effectively therapeutic methods, and the requirement for early diagnosis and comprehensive management of patients with systemic psoriasis. Classification criteria of psoriasis can help to better understand and manage this complex disease comprehensively.